KONSEP HISTORICAL RIGHTS DALAM SENGKETA LAUT TIONGKOK SELATAN BERDASARKAN PUTUSAN PCA CASE NUMBER 2013-19 IN THE MATTER OF THE SOUTH CHINA SEA ARBITRATION BETWEEN THE PHILLIPINES VS CHINA - Kristiyanto Kristiyanto (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2017)
Kristiyanto, Dhiana Puspitawati, SH., LLM., PhD, Agis Ardhiansyah, SH., LLM Fakultas Hukum Universitas Brawijaya Email: kristiyanto1994@gmail.com Â  AbstractI The purpose of this research is to understand Chinaâ€™s historic claim, the status and the purpose of the so-called nine-dashed line map over the islands and maritime areas of the South China Sea and the legal implications for dispute settlement mechanism between ASEAN and China which currently in tough progress. Itâ€™s clear that by virtue of International Law of The Sea (UNCLOS), Chinaâ€™s historic claim over maritime areas (water column, seabed and subsoil, low tide elevations and submerged features), such right is not recognized. While the legal basis of Chinaâ€™s claim is unquestionable, the preliminary findings that led to the hypothesis of this research suggest that Chinaâ€™s historic claim was derived from the concept of historic waters as well as historic title that gives the birth towards the traditional fishing ground alluded on the Article 15 UNCLOS, supported by Chinaâ€™s self-proclaimed occupation of much of the areas of South China Sea for more than 2000 years. This research would also examine the element of â€œhistoryâ€ as the basis of their claim, Chinaâ€™s historic claim comprise of two broad aspect: a historic basis of sovereignty and a historic claim over maritime areas in the South China Sea. China has asserted that they will not participate on the proceedings and neither obey the final decision of the Permanent Court of Arbitration, however such actions is not a bar for the proceedings. On the other hand, the talk between ASEAN and China over the dispute started in 1994 but give no clear direction upon the binding-agreement of the Code of Conduct (COC) between two parties. The willingness of the parties to bind themselves emerged on the 2002 Declaration of Conduct, but the slow progress has worsen the situation and many unanswered problems still remained, hence, this research would also examined the dispute settlement mechanism of the two parties by focusing the discussion on the internal problems within ASEAN. The method used on this research is juridical normative combined with statute approach and conceptual approach. The research will then deeply analyze the relevant document as the primary legal material such as the Tribunal verdict of PCA Case Number 2013-19 Arbitration between China and the Phillipines, United Nations Convention on the Law of the Sea (UNCLOS), ASEAN Charter, Declaration of Conduct 2002. The secondary legal material includes Journal from legal scholars, relevant and credible sources from the internet as well as other relevant documents. The research concluded that the term and the usage of historic rights could not be partially applied to specific things, but shall cover the entire sovereignty of their claimed-area comprehensively. In regards to ASEAN, the research showed that there is an internal issue of disunity and distrust among ASEAN member states, it is stipulated by the decisions of the Phillipines of bringing the case before the PCA without prior negotiation as what agreed on the consensus principle of the member states. Keywords : Chinaâ€™s claim, South China Sea, Historic Right, ASEAN